Upstream Upper-Intermediate B2+. Teachers Book - Evans, V., Obee, B. (Newbury Express Publishing, 2008)
Upstream Upper-Intermediate B2+ is a modular secondary-level course for learners of the English language at upper-intermediate level. The series combines active English learning with a variety of lively topics presented in themed units.
Keywords: English Practice